Contractual formalities in modern contracting. No oral modification clauses and the doctrine of venire contra factum proprium as a limit to its enforceability - Momberg Uribe, Rodrigo (2023)
Although the principle of consensualism is still the general rule in modern contracting, it is common, especially in complex and long-term commercial contracts, to include clauses limiting the parties’ freedom to modify or terminate them, unless certain formalities are observed. In this context, this paper analyses the so-called “no oral modification” clauses, putting forward the arguments for accepting their enforceability, as well as their limits, by means of the application of the doctrine of venire contra factum proprium.